Perancangan Booklet Company Profile sebagai Media Promosi PT. Citra Inovasi Prima - Prasetya Pancatri Ayuda; Juli Atika (Publikasi Indonesia, 2022)
Citra Innovation Prima, which is located in Medan, North Sumatra, is one of the companies engaged in contracting including HVAC (Heating, Ventilation, and Air Conditioning). This company needs a promotion, given the increasing number of competition in terms of HVAC contractor services. Making this design aims to create promotional media in the form of a company profile booklet containing information about a company that can promote the services offered through promotional media made to the audience. The design method is carried out using qualitative and deductive methods through an approach with trusted sources. From the data that has been collected, it will be analyzed using the SWOT method to determine the design concept. The concept displayed is simple and modern in accordance with the current developments. At the design stage explains the steps taken in the design include creative strategies, visual strategies and media strategies. The result of this design is in the form of a company profile booklet that will be printed. It is hoped that this company can use it as a medium in promoting PT. Citra Iovasi Prima to the intended audience.